FOREWORD (Journal of Contemporary Philology, 2025)
This volume presents a series of contributions that address key morphosyntactic, semantic, phonological, and contact-induced phenomena in the languages and dialects of the Balkans. The eight studies collected here examine diverse linguistic structures within a shared areal and typological context, offering new data and analyses that contribute to our understanding of the Balkan Sprachbund and its internal diversity.
Keywords: FOREWORD